Hedge de preços via B3 na comercialização de soja no Brasil: um panorama de sua baixa utilização pelos produtores - Durante, Fernanda Zanella (Universidade do Vale do Rio dos Sinos, 2019)
The present work approaches the behavior of the soy producers in regard to the stock exchange derivatives. One tries to contribute to the growing literature about hedge and the management on agricultural risks when carrying out a revision of literature of how the farmers behave in many regions of the world in regard to the use of derivativos in order to get protection from the variation of the price of the product, trying to innovate when researching a construct not often approached: hedge in soy in Brazil. One revised the literature by using theoretical predictions as well as empirical works in order to create a model of regression which could explain which variables could impact in the non use of stock exchange derivatives. Besides the regression, a set of hypothesis were tested with the aim of observing whether there was a difference between soy producers who do not operate from the one that operate with derivatives. A survey have a sample of 358 soy producers that do not operate in bolsa were used to carry out the regression called general linear models (MGL in Portuguese) and the total sample with 412 answers was used for this test of hypothesis Kruskay-Waills. After the use of this statistical tests, one concluded that state variables that have impact in the non-use of the share market with the purpose of hedge are: size of the property and state experience All of this is a producer perception of who should operate time and dedication perception from who should operate the aversion to risk. In regards to the states of hypothesis one realize that there was a significant difference to the variables: experience, schooling, size of property an excess of confidence.
Keywords: Hedge; Gerenciamento de riscos; Soja; Hedge; Risk management; Soy; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis